Autism Spectrum Disorder (Bangladesh Journal of Child Health, 2019)
Autism spectrum disorder (ASD) is the name for a group of developmental disorders. ASD affects social interaction, communication, interests and behavior. It includes a wide range, “a spectrum,” of symptoms, skills, and levels of disability. It affects how a person acts and interacts with others, communicates, and learns. Children with ASD might have problems talking with others, or they might not look in the eye when one talks to them. They may often seem to be in their “own world.” People with ASD often have these characteristics: ongoing social problems that include difficulty communicating and interacting with others; repetitive behaviors as well as limited interests or activities; symptoms that typically are recognized in the first two years of life; symptoms that hurt the individual’s ability to function socially, at school or work, or other areas of life. Some people are mildly impaired by their symptoms, while others are severely disabled. According to the Centers for Disease Control and Prevention (CDC) around 1 in 68 children has been identified with some form of ASD. The symptoms are present before three years of age, although a diagnosis can sometimes be made after the age of three. More boys are diagnosed with the condition than girls. There is no “cure” for ASD, but speech and language therapy, occupational therapy, educational support, plus a number of other interventions are available to help children and parents.Bangladesh J Child Health 2019; VOL 43 (1) :41-48